Vitamin D – beyond skeletal activities - Dytfeld, Joanna; Horst-Sikorska, Wanda (Menopause Review/Przegląd Menopauzalny, 2013)
Vitamin D is a well-known factor necessary for the proper functioning of the mineral and bone metabolism. Its deficiency plays a well documented role in the pathogenesis of diseases common for endocrinology, gynecology and rheumatology, such as rickets, osteomalacia and osteoporosis. The main source of vitamin D in humans is cutaneous synthesis. Despite the lack of commonly accepted definition of an “optimal” levels of serum vitamin D, many published papers have reported high prevalence of hypovitaminosis D all over the world. Polish experts recommend implementing the populational strategy of vitamin D supplementation in adults. Postmenopausal women constitute the particulary important group in this context – in this cohort supplementation with vitamin D was beneficial in vertebral and non-vertebral risk reduction. Indirectly, proper vitamin D supply reduces the risk of falling, which is also risk factors for osteroporotic fracture. There is also increasing data on the numerous extraskeletal actions of this fat-soluble vitamin i.a in modulating the immune response, inhibiting neoplasmatic growth, influence on blood pressure and blood glucose level. Hipovitaminosis D has been also linked with increased cardiovascular risk and mortality. Molecular background of these associations remains under dispute. Despite the lack of conclusive data on the effects of cholecalciferol supplementation on the development of these processes, data from observational and cross-sectional studies linking hypovitaminosis D with several pathologies are quite convincing.